Eco air purifier / Anantarajoo Selvarajoo … [et al.] - Selvarajoo, Anantarajoo; Santhanasamy, Piruntha; Ramkumar, Suharasni; Thumilan, Sushmeetha; Arikrishnan, Nisha (Division of Research and Industry Linkages, 2017)
3 in 1 air filter and air humidifier which have their function respectively. Air filter is used to remove the contaminants from the air in the room and provides healthier air in our home and office. It prevent air quality-related health conditions. Air humidifier will help for treating discomfort, indigestion, humidify the air, and keep away the mosquitoes from the room environment, Air humidifier can humidify the surrounding and make the environment clean and fresh. The air humidifier is able to continuously humidify for 10 hours before needing a replenishing. Besides that, the extract of mosquito repeller also use in the product which enable multi-function product. The ingredient for mosquito repeller comes from essential oil like citronella, calendula and clove oil in particular ratios. The cost effective air purifier is easily affordable because it cheap and made from recycle materials. The future plans for the projects minimize the coat and make is more cost effective product.